Postural Muscle Unit Plasticity in Stroke Survivors: Altered Distribution of Gastrocnemius' Action Potentials - Vieira, Taian M.; Lemos, Thiago; Oliveira, Laura A. S.; Horsczaruk, Carlos H. R.; Freitas, Gabriel R.; Tovar-Moll, Fernanda; Rodrigues, Erika C. (Frontiers in Neurology, 2019)
Neuromuscular adaptations are well reported in stroke survivors. The death of motor neurons and the reinnervation of residual muscle fibres by surviving motor neurons, for example, seem to explain the increased density of muscle units after stroke. It is however unknown whether reinnervation takes place locally or extensively within the muscle. Here we combine intramuscular and surface electromyograms (EMGs) to address this issue for medial gastrocnemius (MG); a key, postural muscle. While seven stroke survivors stood upright, two intramuscular and 15 surface EMGs were recorded from the paretic and non-paretic gastrocnemius. Surface EMGs were triggered with the firing instants of motor units identified through decomposition of both intramuscular and surface EMGs. The standard deviation of Gaussian curves fitting the root mean square amplitude distribution of surface potentials was considered to assess differences in the spatial distribution of motor unit action potentials and, thus, in the distribution of muscle units between limbs. The median number of motor units identified per subject in the paretic and non-paretic sides was respectively 2 (range: 1-3) and 3 (1-4). Action potentials in the paretic gastrocnemius were represented at a 33% wider skin region when compared to the non-paretic muscle (Mann-Whitney; P=0.014). Side differences in the representation of motor unit were not associated with differences in subcutaneous thickness (skipped-Spearman r=-0.53; confidence interval for r: -1.00–0.63). Current results suggest stroke may lead to the enlargement of the gastrocnemius muscle units recruited during standing. The enlargement of muscle units, as assessed from the skin surface, may constitute a new marker of neuromuscular plasticity following stroke.